Constraining Southern Ocean CO2 flux uncertainty using uncrewed surface vehicle observations - Sutton, AJ; Williams, NL; Bronte Tilbrook (2021)
Remote, harsh conditions of the Southern Ocean challenge our ability to observe the region’s influence on the climate system. Southern Ocean air-sea CO 2 flux estimates have significant uncertainty due to the reliance on limited ship-dependent observations in combination with satellite-based and interpolated data products. We utilize a new approach, making direct measurements of air-sea CO 2 , wind speed, and surface ocean properties on an Uncrewed Surface Vehicle (USV). In 2019, the USV completed the first autonomous circumnavigation of Antarctica providing hourly CO 2 flux estimates. Using this unique data set to constrain potential error in different measurements and propagate those through the CO 2 flux calculation, we find that different wind speed products and sampling frequencies have the largest impact on CO 2 flux estimates with biases that range from −4% to +20%. These biases and poorly constrained interannual variability could account for discrepancies between different approaches to estimating Southern Ocean CO 2 uptake.